Effect of Working Capital Management on The Financial Performance of Banks: An Empirical Analysis for Banks Listed on The Iraq Stock Exchange - Hariem A. Abdullah; Heshoo G. Awrahman; Hardi A. Omer (QALAAI ZANIST JOURNAL, 2021)
Working capital is a measure indicating the level of efficiency and financial soundness of banks and their ability to meet obligations and liabilities in the short-run. The placement of working capital is one of the basic tasks that fall upon modern financial management because of its possible impact on the banking performance. This research aims to study and analyze the effect of working capital management on the financial performance in banks. The study uses secondary data obtained from the published annual financial reports of 15 banks banks listed in the Iraq Stock Exchange during 2005-2018. The collected panel data is analysed through the use of EVIEWS 10. The study found that there is a clear deficiency of some banking departments about defining a management mechanism and allocating working capital and harnessing its components as effective tools in improving the banking financial performance. Moreover, cash conversion cycle is among the factors that have significant impact on the banking performance. Accordingly, some conclusions were presented, including the interest of banking institutions’ management in allocating working capital well and with the aim of promoting the reality of banking procedures and taking account the process of evaluating financial performance using efficient methods, including those related to the analysis of working capital components